(3GdEYdGe GdfaSj (B/s - (3YejQI, eMehO eMeOs ((3YeGf (B:s (3OGQcfhR GdeYQaI ddfTQ(B;(3OGQ CVhGA GdeYQaI ddfTQ h GdJhRjY ,s, 2021)
(3GdaUd Gdhd GdMQH GdGYdGejI GdfaSjI GdaUd GdKGfj GdGTGYI h OhQgG aj GdMQH GdfaSjI GdaUd GdKGdK OhQ GdGYdGe aj JfejI GdYfa h GdSdhc GdYOhGfj GdaUd GdQGHY GdGYdGe GdJdaRjhfj h JMOjGJ GdJfTFI GdGLJeGYjIGdaUd GdNGeS GdYdGbI Hjf GdGYdGe h GdWad GdaUd GdSGOS OhQ GdGYdGe aj HfGA GdTNUjI h GdeLJeY GdaUd GdSGHY JThjT Gdage GdfaSj ddeQGI aj GdGYdGe GdYQHj GdaUd GdKGef hSGFd GdGJUGd GdMOjKI h aN GdGYdGe GdehLgGdaUd GdJGSY GdGYdGe GdfaSj h GdbOQI Ydi GdJGKjQ GdPgfj GdaUd GdYGTQ GdGYdGe GdfaSj h GdJMQjV GdSdhcjs
(3HjHd(B.:(3U(B.199-208s
Keywords: (3GdEYdGe GdYQHjs; (3GdEYdGe GdfaSjs; (3Yde GdfaS GdSjGSjs